2020
DOI: 10.1088/1742-6596/1492/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the processes of additional phosphate post-treatment of ceria conversion coatings deposited on Al 1050 on their corrosion protective behavior

Abstract: Systematic studies were carried out with respect to the elucidation of the role of additional “post-treatment” immersion phosphate processing on conversion corrosion protective ceria coatings CCOC deposited on aluminium Al 1050. Thereupon, the influence of various compositions of the CCOC as well as the conditions of such treatment were studied, based on solutions of Na3PO4 or NH4H2PO4. The results obtained with respect to the corrosion behavior, respectively the corresponding changes in the chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The similar post-treatment of the system Al(NaOH&HNO3)/CCOC(Ce+Cu) in both types of phosphate solutions leads to a substantial shift of the anodic curves towards a more positive Ecor and a lower icor; III. A characteristic feature of the anodic PDPC is the absence of a zone of passive state, which justifies the consideration that the corrosion potential (Еcor) of the studied systems coincides with the potential of pitting formation (Еpit), which is a prerequisite for the local character of the corrosion process under the conditions of stationary corrosion [2]. These results showed that the phosphated CCOC are not only static barrier coatings, but they change the kinetics of the conjugated electrochemical reactions, i.e., they also determine the electrochemical protection.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The similar post-treatment of the system Al(NaOH&HNO3)/CCOC(Ce+Cu) in both types of phosphate solutions leads to a substantial shift of the anodic curves towards a more positive Ecor and a lower icor; III. A characteristic feature of the anodic PDPC is the absence of a zone of passive state, which justifies the consideration that the corrosion potential (Еcor) of the studied systems coincides with the potential of pitting formation (Еpit), which is a prerequisite for the local character of the corrosion process under the conditions of stationary corrosion [2]. These results showed that the phosphated CCOC are not only static barrier coatings, but they change the kinetics of the conjugated electrochemical reactions, i.e., they also determine the electrochemical protection.…”
Section: Resultssupporting
confidence: 54%
“…Our prior investigation [2] of the potentiodynamic polarization curves (PDPC) of the ongoing cathode and anodic processes in CM established that: I. The deposition of CCOC on Al(NaOH&HNO3) and the sealing of this system in NH4H2PO4 (formation of the mixed system Al(NaOH&HNO3)/CCOC(Ce+Cu)/PhL(NH4H2PO4)) determines the strong influence on the kinetics of the cathode reaction of reduction of oxygen, which enhances the protection degree of this system; II.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of hexavalent chromium is restricted by its high toxicity to humans and environmental contamination. 5 In order to overcome these problems, a number of alternative treatments are proposed using chrome-free solutions such as phosphate (P), 6,7 rare earth salt, 8 permanganate, 9 titanate/zirconate (Ti/Zr), 10,11 and molybdate (Mo). 12,13 However, some problems remain to be solved for these methods.…”
Section: Introductionmentioning
confidence: 99%